Fertilizer storage piles at the Agricultural Engineering Laboratory (1953)
General view of fertilizer storage piles supported between uprights at the U.S. Department of Agriculture's Agricultural Engineering Laboratory. Text accompanying the photograph notes that each row contained a full set of replicates and thus constituted a "block" for analysis.
Keywords: Nitrogen fertilizer industry; United States. Bureau of Chemistry and Soils; Fertilizer industry--Equipment and supplies; United States. Department of Agriculture